Development of dope bismuth sulfide system for thermoelectric application / Fitriani - Fitriani, Fitriani (2019)
Bismuth sulfide (Bi2S3) has attracted increasing attention in thermoelectric investigations due to the availability of raw resources, lowered material and production costs, and environmental friendly compared with Bi2Te3-based materials. Bi2S3 also has a high Seebeck coefficient and low thermal conductivity at room temperature. The main obstacle for further improving its thermoelectric performance is due to its intrinsically high electrical resistivity. Therefore, the main objective of this work is to enhance the thermoelectric performance of Bi2S3 through several strategies. Elemental doping approach was selected to improve the carrier concentration and reduce the electrical resistivity of Bi2S3. Either the single doped system of Bi2-xNixS3, Bi2-xSn3xS3 and Bi2S3+xNiO or double doped system of Bi0.95SbX0.05S3 (X = Ni, Hf, Zn and Sn) were evaluated. Nanostructure and nano-microporous structure methods were chosen to further improve thermoelectric performance through reduction of thermal conductivity. Mechanical alloying (MA) method using high energy ball milling (BM) was applied to produce the nanoparticle powders, which will then be consolidated into bulk thermoelectric materials either through cold pressing or spark plasma sintering (SPS) process. Evidently, it is proved that all the samples exhibited predominant phase of orthorhombic Bi2S3. The use of Ni and Sn dopant atoms with lower valence than Bi host atom which can lead to the formation of interstitial solid solution is an effective strategy to increase the carrier concentration hence decrease the electrical resistivity of Bi2S3. Amongst the investigated samples, Bi1.95Ni0.05S3 SPSed sample exhibited the lowest electrical resistivity of 8.27x10-4 Ω.m at 623 K, and further presented a highest dimensionless figure of merit (ZT) which is 0.38 at 623K. Addition of NiO also had significant effect to reduce the electrical resistivity of Bi2S3 system, which was suppressed iv up to ~ 98% by the addition of 0.5 mol% NiO. Moreover, all NiO added samples showed a relative monotonously constant on electrical resistivity values with increasing temperature. The changing of lattice constant due to substitution or inclusion of dopant atoms into Bi2S3 lattice affected the Seebeck coefficient of Bi2S3 system. Lattice shrinkage due to atomic substitution will increase the effective mass, m*, thus increase the Seebeck coefficient. Bi1.99Ni0.01S3 and Bi1.99Sn0.03S3 which has the smallest volume cell in its system presented the highest Seebeck coefficient values in the whole measured temperature. The highest Seebeck coefficient of -766.15 μV/K at 300 K and -1170.25 μV/K at 323 K were exhibited by Bi1.99Ni0.01S3 and Bi1.99Sn0.03S3, respectively. In the thermal conductivity behaviors, the presence of porous structures give a significant effect on reduction of thermal conductivity, by a reduction of ~59.6% compared to a high density Bi2S3. In addition, the presence of Sb2S3 secondary phase in Bi0.95SbX0.05S3 system contributed on enhancement of phonon scattering hence resulted in the reduction of thermal conductivity. Bi0.95SbNi0.05S3 sample presented the lowest thermal conductivity value which is 0.21 W/mK at room temperature. Conclusively, this works have shown useful results for comprehensive understanding of Bi2S3 as potential material for low to middle temperature thermoelectric energy conversion.